Determinants of Stock Price Volatility: The Role of Sustainability Disclosure in Manufacturing Firms - Denny Putri Hapsari Denny; Denny Kurnia Denny (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study investigates whether earnings volatility, dividend policy, and asset growth affect stock price volatility in Indonesian manufacturing firms and examines the moderating role of sustainability disclosures. Research Methodology: Using secondary data from the annual and sustainability reports of manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, the sample was selected through purposive sampling, resulting in 35 firms (175 firm-year observations). Panel data regression with interaction terms was employed, and model selection tests indicated that the random effects model was the most appropriate. Results: The findings show that earnings volatility and asset growth significantly influence stock price volatility, whereas dividend policy does not have a significant effect. Sustainability disclosure significantly moderates the relationships between earnings volatility and stock price volatility, as well as between asset growth and stock price volatility; however, it does not moderate the dividend policy volatility relationship. Conclusions: Stock price volatility is driven by firm fundamentals and is conditional on a firm’s sustainability transparency. Limitations: This study focuses on manufacturing firms in a single emerging market and measures sustainability disclosure using an index approach that captures the extensiveness rather than the disclosure quality. Contributions: This study enriches capital market research by integrating financial and sustainability information to explain volatility formation.